Group multi-criteria supplier selection using an extended VIKOR method with interval 2-tuple linguistic information. Issue 4 (March 2015) - You, Xiao-Yue; You, Jian-Xin; Liu, Hu-Chen; Zhen, Lu
Highlights Propose an extended VIKOR method for group multi-criteria supplier selection. Diversity and uncertainty of decision makers' assessments are modeled using interval 2-tuples. Multiple and conflicting criteria are considered and evaluated by extended VIKOR method. The new method is more suitable to handle the supplier selection problem under uncertain environment.